Improving Product Quality and Satisfaction as Fundamental Strategies in Strengthening Customer Loyalty - Lina, Roidah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
In the food industry, quality is a product guarantee. That is, the quality in a product is an absolute requirement. Because in reality, consumers will only consume products whose quality is guaranteed. The purpose of this study was to describe the variables of product quality and satisfaction statistically, in order to obtain a quantitative conclusion on increasing customer loyalty. In describing the phenomenon, the research uses a quantitative approach with a causal associative method. The number of respondents in this study were 97 people, namely consumers of PT Kobe Boga Utama, Tangerang Regency. Statistical technique using multiple linear regression with partial and simultaneous testing. The results of the study confirm that mathematically product quality and satisfaction are strong factors that affect loyalty. That is, customers become loyal because their physical and emotional needs are met, and this can be answered by quality and satisfaction.